IMPLEMENTATION OF THE SANOGENETIC INFLUENCE OF HEALTH CARE TECHNOLOGIES ON THE FUNCTIONAL AND RESERVE CAPABILITIES OF THE BODY OF PRESCHOOL CHILDREN - Sumcova, Svitlana; Poimanova, Yuliia; Latina, Hanna (Sworld-Us Conference proceedings, 2022)
The paper examines the assessment of the program of sanogenetic influence of health-saving technologies on the functional and reserve capabilities of the body of preschool children. The implementation of the program of sanogenetic influence of health-pres